2021
DOI: 10.37506/mlu.v21i2.2673
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis of Microplastic in Fish (Nemiptus Japonicas & Rastrelliger Sp.) in Communities in the Coast Area of Tamasaju, Galesong Takalar

Abstract: Plastic waste has become one of the most serious threats to the marine environment. Among the plastic waste of special concern is microplastic because of its small size. This study aimed to analyze the level of risk of microplastic exposure through fish consumption in communities in the coastal area of Tamasaju Village, North Galesong District, Takalar Regency. Microplastic abundance found as many as 18 particles, microplastic types found are the shape of a line or fiber with different color and size variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Both non-carcinogenic or carcinogenic risks indicate the strong relation with the concentration (C) of microplastic in fish, intake rate (R), shelf frequency (FE), exposure duration, and weight (WE) of the respondents. 80 Based on the results of the study, microplastics were found in all feces of samples of pregnant women in the working area of Puskesmas Pattingalloang and Jumpandang Baru, Makassar. Microplastics were found from thirty stool samples ranging from 5-21 microplastics with the types of fibers, fragments, and films due to fish consumption.…”
Section: Discussionmentioning
confidence: 94%
“…Both non-carcinogenic or carcinogenic risks indicate the strong relation with the concentration (C) of microplastic in fish, intake rate (R), shelf frequency (FE), exposure duration, and weight (WE) of the respondents. 80 Based on the results of the study, microplastics were found in all feces of samples of pregnant women in the working area of Puskesmas Pattingalloang and Jumpandang Baru, Makassar. Microplastics were found from thirty stool samples ranging from 5-21 microplastics with the types of fibers, fragments, and films due to fish consumption.…”
Section: Discussionmentioning
confidence: 94%